The impact of COVID-19 on the social and cultural integration of international students: a literature review - Nicolaou, Anna; Sin, Christina; Tavares, Orlanda; Apsite-Berina, Elina; Borras, Judith; Bulut-Sahin, Betul; Chrancokova, Martina; Czerska-Shaw, Karolina; Devlin, Anne Marie; Heinzmann, Sybille; Jokila, Suvi; Keri, Anita; et al. (My University, 2025)
This systematic literature review summarises the state-of-the-art evidence on the impact of COVID-19 on the integration of international students in their host countries and institutions. Conducted between January and May 2022, it analyses the responses to COVID-19 of the key actors involved in international student mobility: national/regional authorities, higher education institutions, and students. Findings reveal that governmental action and institutional measures were decisive in shaping international students’ integration experiences. Regarding governmental action, criticism of the policies adopted by Australia and the USA in relation to immigration and/or support stand out, in contrast to policies adopted by the Canadian authorities. Higher education institutions played an important role in mitigating the negative effects of COVID-19 on international students’ integration. These targeted different needs– material, well-being, and social– through different types of support: logistical and financial support, psychological support, and the provision of platforms for ongoing social interaction and exchange. Most studies, however, focus on the students themselves, the challenges they faced during the pandemic and their coping strategies. Common to international students’ lived experience was (dis)connectedness, with the following themes emerging as obstacles to their social and cultural integration: distress during lockdown periods, disruption of their social life and support networks, mental health issues, discrimination and racialised prejudice, and language barriers. The review concludes by proposing recommendations and by identifying avenues for future research.
Keywords: International students; Integration; COVID-19; National policies; Institutional support